Reconstruction and Future Prediction of the Distribution of Wetlands in China. Issue 11 (5th November 2018) - Xue, Zhenshan; Zou, Yuanchun; Zhang, Zhongsheng; Lyu, Xianguo; Jiang, Ming; Wu, Haitao; Liu, Xiaohui; Tong, Shouzheng
Abstract: Due to lack of historical and accurate data, less well known is how the wetlands of China were changed and affected by human disturbance and climate change during past millennia and also, whether climate warming could impact the surviving wetlands in China. Using niche‐based distribution models and downscaled climate data of the past and future, we projected the potential distribution of wetlands in China. Our results show that more than half of the wetlands in China have been destroyed over the past few millennia. Also, future warming will have a negative effect on remaining wetlands. Freshwater swamp and seasonal salt marsh are predicted to dramatically reduce under future scenarios. Wetlands in high mountain regions and inland arid regions are under threat of degeneration and water salinization. This research could provide valuable information for the future conservation and management of wetlands in China. Plain Language Summary: In this research, we predicted how many wetlands of China have disappeared during the past 6, 000 years. We also predicted how many wetlands in China will be at the risk of disappearing in the future. We found that half of the wetlands in China have been destroyed during the past 6, 000 years. Main reason is human activities such as farming and urban expansion. We also found that future climate changes would impact remaining wetlands in China. Key Points: We used niche‐based distribution models to assess the potential projected the potential distribution of wetlands in China from Mid‐Holocene to 21st century More than half of wetlands in China have been destroyed over the past few thousand years Future warming will have a negative effect on remained wetlands